Pollen transfer networks reveal alien species as main heterospecific pollen donors with fitness consequences for natives. (26th October 2020) - Parra‐Tabla, Víctor; Alonso, Conchita; Ashman, Tia‐Lynn; Raguso, Robert A.; Albor, Cristopher; Sosenski, Paula; Carmona, Diego; Arceo‐Gómez, Gerardo
Abstract: The ecological dynamics of co‐flowering communities are largely mediated by pollinators. However, current understanding of pollinator‐mediated interactions primarily relies on how co‐flowering plants influence attraction of shared pollinators, and much less is known about plant–plant interactions that occur via heterospecific pollen (HP) transfer. Invaded communities in particular can be highly affected by the transfer of alien pollen, but the strength, drivers and fitness consequences of these interactions at a community scale are not well understood. Here we analyse HP transfer networks in nine coastal communities in the Yucatan Mexico that vary in the relative abundance of invasive flowers to evaluate how HP donation and receipt varies between native and alien plants. We further evaluate whether HP donation and receipt are mediated by floral traits (e.g. display, flower size) or pollinator visitation rate. Finally, we evaluated whether post‐pollination success (proportion of pollen tubes produced) was affected by alien HP receipt and whether the effect varied between native and alien recipients. HP transfer networks exhibit relatively high connectance ( c . 15%), suggesting high HP transfer within the studied communities. Significant network nestedness further suggests the existence of species that predominantly act as HP donors or recipients in the community. Species‐level analyses showed that natives receive 80% more HP compared to alien species, and that alien plants donate 40% more HP than natives. HP receipt and donation were mediated by different floral traits and such effects were independent of plant origin (native or alien). The proportion of alien HP received significantly affected conspecific pollen tube success in natives, but not that of alien species. Synthesis . Our results suggest that HP transfer in invaded communities is widespread, and that native and alien species play different roles within HP transfer networks, which are mediated by a different suite of floral traits. Alien species, in particular, play a central role as HP donors and are more tolerant to HP receipt than natives—a finding that points to two overlooked mechanisms facilitating alien plant invasion and success within native co‐flowering communities. Abstract : Native and alien plant species play different roles within heterospecific pollen transfer networks in invaded communities. Alien species, in particular, play a central role as HP donors and are more tolerant to HP receipt than natives—a finding that points to two overlooked mechanisms facilitating alien plant invasion and success within native co‐flowering communities. Resumen: La dinámica de las comunidades co‐florales son en gran medida mediadas por los polinizadores. Sin embargo, mucho del conocimiento actual de las interacciones mediadas por polinizadores se basa en cómo plantas que co‐florecen influencian la atracción de polinizadores y su compartición, pero se conoce mucho menos acerca de las interacciones que ocurren vía la transferencia de polen heteroespecífico (HP). En particular las comunidades invadidas pueden ser muy afectadas por la transferencia de polen invasor, no obstante, la fuerza, los factores que lo median y las consecuencias en la adecuación de estas interacciones a escala comunitaria han sido escasamente estudiadas o poco comprendidas. Aquí analizamos las redes de transferencia de HP en nueve comunidades costeras en Yucatán México, que varían en la abundancia relativa de flores invasoras, para evaluar como la donación y recepción de HP varía entre especies nativas y especies invasoras. Además, evaluamos si la donación de HP y su recepción son mediados por rasgos florales (e.g. número y tamaño de las flores) o por la tasa de visitantes florales. Finalmente, evaluamos si el éxito post‐polinización (proporción de tubos polínicos) es afectado por el HP invasor y si este efecto variaba entre especies receptoras nativas o invasoras. La red de transferencia de HP mostró una relativamente alta conectancia ( ca . 15%), sugiriendo una alta transferencia de HP dentro de las comunidades estudiadas. El anidamiento significativo de la red sugirió la existencia de especies que predominantemente actúan como donadoras o recipientes de HP dentro de las comunidades. Análisis a nivel de especies mostraron que las especies nativas reciben 80% más HP comparado con las especies invasoras, y que las especies invasoras donan 40% más que las nativas. La recepción o donación de HP estuvieron mediadas por diferentes rasgos florales y sus efectos fueron independientes del origen de las plantas (nativas o invasoras). La proporción de HP invasor recibido afectó el éxito en la formación de tubos polínicos conespecíficos en las especies nativas, pero no en las invasoras. Síntesis . Nuestros resultados sugieren que la transferencia de HP en comunidades invadidas es común, y que las especies nativas y las invasoras juegan diferentes papeles en las redes de transferencia de HP, los cuales son mediados por diferentes grupos de caracteres florales. En particular las especies invasoras juegan un papel central como donadoras de HP y son más tolerantes a su llegada que las especies nativas, un hallazgo que subraya dos mecanismos poco estudiados que facilitan la invasión de plantas y su éxito en las comunidades co‐florales.